Use of digital tools in Kenya’s potato value chains: Qualitative perspectives from a field visit in Nakuru County - Boukaka, Sedi Anne; Azzarri, Carlo (International Food Policy Research Institute, 2024)
Potato farmers in Kenya face a multitude of challenges throughout the value chain, including limited access to quality seeds and fertilizers, inadequate storage and postharvest handling facilities, and fluctuating market prices. These issues are particularly acute for women and youth, who face additional barriers due to persistent social inequalities in the agricultural sector. Digital tools—such as smartphones, smart sensors, or tools involving remote sensing and GIS mobile mapping, as well as applications for agricultural information, e-marketplaces, e-learning platforms, and digital financing platforms—hold significant potential to address these challenges. For instance, these tools can provide access to valuable agricultural information, weather forecasts, and best management practices, helping farmers make in formed decisions and improve crop management. Mobile apps and platforms can facilitate market access by connecting farmers directly with buyers, which can reduce price fluctuations and ensure fair returns on their produce through price information. Digital tools can also play a crucial role in addressing post harvest losses by providing real-time monitoring and management of storage conditions, helping farmers optimize storage to reduce spoilage and wastage. Additionally, digital platforms can provide farmers with information on proper postharvest handling techniques, including sorting, grading, and packaging, to ensure that potatoes are well processed, prepared, packaged, and marketed with minimal losses. However, the adoption of these tools has been slow in Africa south of the Sahara, hindered by infrastructural gaps, high costs, and low digital literacy, thereby limiting their scalability and impact (Aker et al. 2016, Aker and Cariolle 2022, Abate et al. 2023).